The senseless man and his fear of freedom: Kafkaesque thought through the mind of Erich Fromm, a premonition of our times - Padilla Díaz, Jorge (2023)
In The Fear of Freedom, first published in 1941, German psychoanalyst Erich Fromm unmasks the ambivalent tendencies that have ingrained modern societies: the liberties achieved by the average individual citizen of democracies reliant on capitalism are directly proportional to the growth of universally experienced loneliness, insignificance, and fragility. This exhausting situation inevitably pushes the individual to seek some form of subterfuge or palliative to try and counter a growing feeling of anguish that seems to be innate, all-encompassing. This essay addresses the correlation between the absurd coherence of the Kafkaesque universe and Fromm’s claims regarding the mechanisms and crushing feelings —exacerbated by the spirit of latestage capitalism that plagues modern Western societies— first developed in Protestant ethics and discusses them regarding the problems of our times. One of the most recognizable and impactful, rational-yet-irrational ideas that stands out from Kafka’s work is the “unconscious fear of freedom” that forces his characters to lock themselves up within the absolute prison of submission —as Fromm would put it— to the tremendous Other and the established social norms. This isolated refuge individuals have created to shield themselves from the chaotic, unstable, external reality comes at the expense of the personage’s physical well-being (evidently seen in The Metamorphosis or A Hunger Artist) and psychological well-being (shown in The Castle or The Trial).